Developing COVID-19’s Vaccines: Short Review - Alsayed, Raghda; Kadhom, Mohammed; Salman, Israa; Albaker, Tariq; Hairunisa, Nany; Amalia, Husnun; Yousif, Emad (Al-Nahrain Journal of Science, 2022)
Background. Since humanity is attempting to challenge the COVID-19 pandemic by accelerating the production of vaccines against SARS-CoV-2, there could be opposite health side-effects on the participants and researchers. Materials and Methods: Institutions, governments, companies, and organizations around the world work relentlessly to produce drugs and/or vaccines for this disease; yet none were approved. In this work, we are presenting the technologies platforms, developed vaccines, development challenges, and the under-process vaccines. Results: The recent developments in the diagnosis and types of vaccines were also discussed. Conclusion: Many vaccines were invented to stop COVID-19’s spreading using different techniques.